Endogenous enkephalin is necessary for cocaine-induced alteration in glutamate transmission within the nucleus accumbens - Mongi Bragato, Bethania del Carmen (2021)
Altered glutamate transmission within the nucleus accumbens (NAc) has been proposed as a central mechanism underlying behavioural sensitisation associated with repeated cocaine exposure. In addition to glutamate, enkephalin, an endogenous opioid peptide derived from proenkephalin, is necessary for the neuroadaptations associated with chronic cocaine. However, the influence of enkephalin on long-term changes in glutamate transmission within the NAc associated with cocaine-induced sensitisation has not been described. This study used knockout proenkephalin mice (KO) to study the influence of endogenous enkephalin on the adaptations in glutamate neurotransmission associated with repeated cocaine treatment. Wild-type (WT) and KO mice were treated with daily cocaine injections for 9 days to induce sensitisation. On days 15 and 21, the animals received a cocaine challenge and locomotor sensitisation was evaluated, and microdialysis was performed to determine accumbens glutamate content on day 21. No expression of behavioural sensitisation to cocaine was evidenced in the KO mice. Consistently, these showed no changes in glutamate transmission in the NAc associated with repeated cocaine. This study reveals the central role of enkephalin in regulating the glutamate mechanisms associated with cocaine sensitisation.